Análise do desenvolvimento de filme de líquido em escoamento ascendente sob efeito dos campos centrífugo e gravitacional - Eidt, Henrique Krainer (2017)
Flows with free surface compose an important class of two-phase flows in the fluids mechanics. In various applications a thin film of liquid builds up on horizontal or vertical surfaces. This type of flow is denominated as liquid film flow. The present work contemplates the analysis of the development of liquid film in ascendant flow under the action of the centrifugal and gravitational fields, located in a cyclonic chamber of a distribution system. In the study, the dynamics of a liquid film flow were analyzed with the aid of three-dimensional and transient numerical simulations. The numerical model developed was validated based on experimental data provided by NUEM (Centre for Multiphase Flows). In the numerical modeling of the flow, were used the EulerianEulerian two fluid model coupled with the compressive discretization scheme for the capture of the liquid-gas interface and the Shear Stress Transport turbulence model. The balance equations were discretized using the finite volume based on finite elements method. Numerical simulations were supported by the commercial software ANSYS-CFX 15.0. The results obtained in this work enabled the understanding of flow dynamics (formation, spreading, stability and development) and how the superficial velocities of liquid and gas (0.5, 1.0, 1.5 and 2.0 m/s for both phases) influence on the stability and behavior of the ascendant liquid film flow. A mathematical model capable of providing conditions that represent the average behavior of a slug flow pattern was also elaborate.